2017
DOI: 10.1088/1361-6463/aa875a
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal characterization of the multiple current pulse regime of diffuse barrier discharges in helium with nitrogen admixtures

Abstract: This work reports on the spatio-temporal characterization of the multiple current pulse regime of diffuse barrier discharges driven by sine-wave feeding voltage at a frequency of 2 kHz in helium with small nitrogen admixtures. The discharge gap of 3 mm is bounded by glass plates on both plane electrodes. Priority is given to the lateral discharge inhomogeneities, underlying volume-and surface-memory effects, and the breakdown mechanism. Therefore, relevant processes in the discharge volume and on the dielectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…The critical function of these two algorithms is to establish a transformation between surface charge density on dielectrics and induced electric field in Pockels crystals. It should be noted that the directly calculated surface charge density is not equal to the actual one in most cases unless the phase retardation induced by the applied voltage between two electrodes is subtracted [45,54]. A common practice is to deduct a virtual surface charge distribution numerically calculated by surface electric field distribution under the boundary condition of measured applied voltage on electrodes.…”
Section: Discussion On Two Inversion Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The critical function of these two algorithms is to establish a transformation between surface charge density on dielectrics and induced electric field in Pockels crystals. It should be noted that the directly calculated surface charge density is not equal to the actual one in most cases unless the phase retardation induced by the applied voltage between two electrodes is subtracted [45,54]. A common practice is to deduct a virtual surface charge distribution numerically calculated by surface electric field distribution under the boundary condition of measured applied voltage on electrodes.…”
Section: Discussion On Two Inversion Algorithmsmentioning
confidence: 99%
“…Minimum shutter duration of cameras √ Equip ultra-fast imaging technologies [41] Narrowest pulse width of light sources √ Adopt ultra-short pulse LED or laser sources [53] Charge resolution Thickness of tested samples √ Prepare thinner film or plate samples [54] Half-wave voltage of Pockels cells √ Utilise frequency-domain 2D Flourier transform inversion algorithm [46] Anti-noise surface charge inversion algorithms Effective area Maximum area of Pockels crystals √ Replace with needle or transparent electrodes [55] Blockage in light path by electrodes √ Control induced electric field at 45°to light path [50] √ Operate in reflection-type measurement systems [56] Charge range Wavelength of light sources √ Use lasers or LED sources with larger wavelengths [27] Electro-optic coefficient of Pockels crystals…”
Section: Time Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key effect of the additional nitrogen is regarded to stimulate Penning ionisation, thereby facilitating volume ionisation and the consequent MCP discharge. In 2017, Bogaczyk et al [111] also presented a thorough experimental study on the spatio-temporal characterisation of the MCP regime of diffuse DBD in helium with small nitrogen admixtures. They also observed that the number of current pulses per half cycle rises with the increase of nitrogen admixture due to the predominant role of Penning ionisation.…”
Section: Mcp Behaviours From Experimentsmentioning
confidence: 99%
“…2(b)-(d). The multiple discharge phenomenon can be explained through the evolution of the gas voltage induced by both the accumulated charge and the applied voltage [38]. While d increases and exceeds 40 mm, it is difficult to generate the discharges.…”
mentioning
confidence: 99%